A baseline audit of post-vasectomy follow-up at three Cape Town district health facilities - Michael L. le Roux; Renaldo Christoffels; Roland Kroukamp; Jennie Morgan; Omotayo S. Alaofin; Tasleem Ras; Klaus B. von Pressentin (South African Family Practice)
Background: Our study focuses on vasectomies, an underutilised contraception method worldwide. Little is known about post-vasectomy semen analysis (PVSA) adherence in our setting, which is an essential step in confirming the procedure’s success. We aimed to describe patient adherence to post-vasectomy follow-up and the success of procedures performed by different surgeon categories at three Cape Town district health facilities.